1976
DOI: 10.1007/bf02777374
|View full text |Cite
|
Sign up to set email alerts
|

Sibling cases of chronic recurrent hepatocerebral disease with hypercitrullinemia

Abstract: Two sibling cases with chronic recurrent hepato-cerebral syndrome which correspond to the nutritional form of hepato-cerebral disease entitled by Shikata et al. and the data of plasma free aminoacids analyses of these cases were reported. The one case is 27 years old male and the other case is 36 years old female. Their parents were cousins. Both cases have had unbalanced diet, especially liked legumes unusually. Their main symptom was recurrent disturbance of conciousness and convulsive seizures. Slight abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, there are no abnormalities in hepatic ASS mRNA or within the ASS gene locus (Sase et al 1985;Kobayashi et al 1986Kobayashi et al , 1993, and the primary defect of CTLN2 has been unknown for a long time. We have noted that 26 of 132 CTLN2 patients (24 of 126 families) are apparently from consanguineous parents (Kobayashi et al 1993), and sibling cases have been found (Tsujii et al 1976;our unpublished data), suggesting that CTLN2 is an autosomal recessive disorder. Most recently, we have identified the CTLN2 locus on chromosome 7g21.3 by homozygosity mapping analysis of 18 individuals from consanguineous unions, a novel SLC25A 13 gene by positional cloning, and five different DNA sequence alterations that account for the mutations in the 18 CTLN2 patients examined .…”
Section: Introductionmentioning
confidence: 91%
“…However, there are no abnormalities in hepatic ASS mRNA or within the ASS gene locus (Sase et al 1985;Kobayashi et al 1986Kobayashi et al , 1993, and the primary defect of CTLN2 has been unknown for a long time. We have noted that 26 of 132 CTLN2 patients (24 of 126 families) are apparently from consanguineous parents (Kobayashi et al 1993), and sibling cases have been found (Tsujii et al 1976;our unpublished data), suggesting that CTLN2 is an autosomal recessive disorder. Most recently, we have identified the CTLN2 locus on chromosome 7g21.3 by homozygosity mapping analysis of 18 individuals from consanguineous unions, a novel SLC25A 13 gene by positional cloning, and five different DNA sequence alterations that account for the mutations in the 18 CTLN2 patients examined .…”
Section: Introductionmentioning
confidence: 91%
“…Most patients are thin, more than 90% showing a body mass index less than 20, and about 40% show an index less than 17. Pancreatitis, hyperlipidemia, and hepatoma are the major complications of CTLN2 Ikeda et al 2001;Tsujii et al 1976). …”
Section: Clinical Features Of Ctln2mentioning
confidence: 99%
“…These phenomena are useful for diagnosis of CTLN2 Tsuboi et al 2001;Ikeda et al 2001;Maruyama et al 2001;Oshiro et al 2002) and to determine the prognosis of the patients (Yagi et al 1988), and may be related to the finding that about 10% of the patients with CTLN2 suffer from hepatoma without liver cirrhosis at relatively young ages (Tsujii et al 1976;Kobayashi et al 2000).…”
Section: Questions To Be Answeredmentioning
confidence: 99%
“…In most cases patients were infants and died within childhood but some of them survived to adulthood (Scott-Emuakpor et al 1972). On the other hand, in the field of internal medicine and psychiatrics, citrullinemia with no signs nor symptoms until adulthood has been known (Tsuji et al 1976;Yamauchi et al 1980). In this paper such a case was called "adult type" and the patient is just an adult-type citrullinemia.…”
Section: Discussionmentioning
confidence: 98%
“…1972; Koyama et al 1973). Recently these cases have been shown to have an increased level of serum citrulline and some investigators proposed the abnormality of urea cycle as the etiology (Tsuji et al 1976; Yamauchi et al 1980). The congenital hyperammonemia resulting from the urea cycle abnormality is known among pediatricians (Hsia 1974) and there were some patients who survived to adulthood (ScottEmuakpor et al 1972;Fell et al 1974).…”
mentioning
confidence: 99%